Tapered Plastic Optical Fiber Coated With Al-Doped ZnO Nanostructures for Detecting Relative Humidity - Harith, Zuraidah; Ninik, Irawati; Hartini, Ahmad Rafaie; Batumalay, Malathy*; Sulaiman, Wadi Harun; Roslan, Md Nor; Ahmad, Harith (IEEE, 2015)
A relative humidity (RH) sensor is demonstrated using a tapered plastic optical fiber (POF) that is coated with Al-doped ZnO nanostructures. A simple etching method was used to fabricate the tapered POF that operates based on intensity modulation technique. The tapered fiber was then coated with Al-doped ZnO nanostructures using sol-gel immersion method with different mol% of Al nitrate that acts as a dopant. The 1 mol% of Al nitrate that used in the synthesis process exhibited better performance compared with the other doping concentrations. Then, results obtained for both undoped ZnO and 1 mol% of Al-doped ZnO were compared and investigated. The performance of 1 mol% of Al-doped ZnO demonstrated better linearity and sensitivity of 97.5% and 0.0172 mV/%, respectively, whereas the undoped ZnO yielded linearity and sensitivity of 93.3% and 0.0029 mV/%, respectively. The proposed sensor provides numerous advantages, such as simplicity of design, low cost of production, higher mechanical strength, and is easier to handle compared with silica fiber optic. Results show that tapered POF with Al-doped ZnO nanostructures enables the increase in sensitivity of fiber for detection of changes in RH.